Analysis of Natural Selection of Immune Genes in Spinibarbus caldwelli by Transcriptome Sequencing - Tuo, Yun; Chu, Wuying; Zhang, Jianshe; Cheng, Jia; Chen, Lin; Bao, Lingsheng; Xiao, Tiaoyi (Frontiers in Genetics, 2020)
Spinibarbus caldwelli is an omnivorous cyprinid fish that distributes widely in China. To investigate the adaptive evolution of S.caldwelli, the transcriptome was sequenced by Illumina HiSeq 4000 platform. A total of 80,447,367 reads were generated by Next Generation Sequencing. Also, 211,386 unigenes were obtained by de novo assembling. Additionally, we calculated that the divergence time between S.caldwelli and Sinocyclochellus grahami is 23.14 million years ago. And both of them were apart from Ctenopharyngodon idella in 46.95 million years ago. Furthermore, 38 positive genes were identified by calculating of Ka/Ks ratio from 9225 orthologs. Among them, several immune-related genes were identified as positively selected genes, such as POLR3B, PIK3C3, TOPORS, FASTKD3, CYPLP1A1, and UACA, indicating that immune system genes met a great variation under environment selection. All our results throw light on the nature of the natural selection of S. caldwelli and contribute to future immunological and transcriptome studies.